WEB-BASED INVENTORY INFORMATION SYSTEM AT SMA NEGERI 1 BABAKANCIKAO PURWAKARTA: WEB-BASED INVENTORY INFORMATION SYSTEM AT SMA NEGERI 1 BABAKANCIKAO PURWAKARTA - Nanang Mulyana, Nanang Mulyana; Rahmah, leny Saili; Aminah, Siti (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2023)
Digitalization is very important at this time, including in the education sector. Education has complex activities, starting from processes, education systems, curriculum, administration and other things. The success of education is greatly influenced by the speed of the interaction process which can be replaced by an information system. One of the important activities in the education sector that needs to be implemented is an information system, namely inventory of goods. This affects information on the availability of facilities and infrastructure, their condition and even their quantity. So an information system is needed to digitize the inventory of goods at the school, namely SMA Negeri 1 Babakancikao Purwakarta. This information system uses supporting tools, namely phpmyadmin, MySQL, XAMPP and Sublime Text. The result of this research is a web-based goods inventory application at SMA Negeri 1 Babakancikao Purwakarta which consists of 11 menus including: 1) login page; 2) main menu page; 3) brand page; 4) category pages; 5) item page, 6) user page; 7) incoming goods page; 8) outgoing goods page; 9) incoming goods report page; 10) outgoing goods page, and 11) stock report page. This system has made it easier for school employees/staff to record inventory and also makes it easier to monitor inventory.